The Dental Pulp Biology, Pathology, and Regenerative Therapies - Goldberg, Michel.; Goldberg, Michel. (Springer Berlin Heidelberg : Imprint: Springer, 2014)
This book provides a detailed update on our knowledge of dental pulp and regenerative approaches to therapy. It is divided into three parts. The pulp components are first described, covering pulp cells, extracellular matrix, vascularization, and innervation as well as pulp development and aging. The second part is devoted to pulp pathology and includes descriptions of the differences between reactionary and reparative dentin, the genetic alterations leading to dentinogenesis imperfecta and dentin dysplasia, the pulp reaction to dental materials, adverse impacts of bisphenol A, and the effects of fluorosis, dioxin, and other toxic agents. The final part of the book focuses on pulp repair and regeneration. It includes descriptions of various in vitro and in vivo (animal) experimental approaches, definition of the pulp stem cells with special focus on the stem cell niches, discussion of the regeneration of a living pulp, and information on new strategies that induce pulp mineralization.